Accounting policy of receivables at construction enterprises - Ivanova, T.N. (Ways to Improve Construction Efficiency, 2020)
Analysis of existing approaches to the organization of accounting processes at the enterprise shows that an important element of the accounting policy of the construction company is to create approaches to accounting for receivables in the system of settlements with customers and its reflection in the financial statements. The formed accounting policy on receivables significantly affects the value of financial condition and performance of the enterprise. The purpose of the study is to analyze existing approaches to determining the accounting policy in terms of receivables, improving the accounting process and improving the efficiency of settlements in construction companies in modern business conditions. The article considers the existing requirements of the legislation on the accounting policy of settlement operations of the enterprise, the procedure for creating a reserve for doubtful debts, receivables write-off. The provisions of the accounting policy of receivables proved needed to be clarified and detailed in order to improve the efficiency of settlement management and financial condition of the enterprise. It is proposed to develop a work plan of accounts, job descriptions of the accountant for settlement operations, document flow schedule (in particular in terms of settlement operations), registers of analytical accounting of receivables and other applications that directly regulate the accounting of receivables in the system of settlements with buyers. enterprise. The proposed elements of the accounting policy relate to the debts of customers and are subject to disclosure in the Order on the accounting policy of the enterprise. Adherence to the developed elements of accounting policy will provide reliable information on the company's settlements with debtors, rationally organize the accounting of receivables in the system of settlements with customers, to obtain reliable and complete information about the debt.